2023
DOI: 10.1007/s43615-023-00290-1
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behavior as a Challenge and Opportunity for Circular Food Packaging—a Systematic Literature Review

Abstract: The food sector has been targeted as a potential site for the implementation of circular economy strategies. Food packaging, in particular, has caused concern due to its high production volume, short usage time, and problems related to waste management and littering. Circular economy strategies could potentially address these concerns if there is consumer acceptance and participation in circular systems. The present review seeks to inform future studies of the need for further research in this area by reviewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Research on reusable packaging has reemerged starting in 2018, showing consumers' acceptance of this type of packaging [19]. Long et al [20] reported that English consumers are in favor of reusable food product packaging strategies.…”
Section: Literature Review On Consumers' Behavior Toward Environmenta...mentioning
confidence: 99%
“…Research on reusable packaging has reemerged starting in 2018, showing consumers' acceptance of this type of packaging [19]. Long et al [20] reported that English consumers are in favor of reusable food product packaging strategies.…”
Section: Literature Review On Consumers' Behavior Toward Environmenta...mentioning
confidence: 99%